Research on the Evaluation Index of Grid Enterprises' Innovation Index Based on the Same Industry Benchmark. Issue 5 (July 2020) - Chang, Yan; Meng, Weixuan
Abstract: Based on the in-depth analysis and construction of the technology innovation index and evaluation system that meet the characteristics of power grid enterprises, this paper studies the key technical issues involved in the technology innovation index system of different types of units, such as indicator dimension, indicator type, indicator application, indicator management, application technology route and evaluation results. By constructing an evaluation index system for the technology innovation index of power grid companies, this paper proposes a linkage strategy between the index and technology innovation management, promptly discovers the gaps, diagnoses the cause of the problem, formulates effective countermeasures, provides effective technical support and systematic decision-making basis.